Design of a Web-Based Application for Business Enrollment Number (NIB) Recording at the Prabumulih City Dpmptsp - Ramadhan Syahputra; Muchlis; Phinton Panglipur (Yayasan Kita Menulis, 2026)
This proposal aims to design and develop a web-based application for recording and reporting Business Identification Numbers (NIB) at the Investment and One-Stop Integrated Service (DPMPTSP) of Prabumulih City. Currently, the process of recording NIBs is done manually using a report book and Microsoft Excel, which can lead to errors, inefficiencies, and difficulty in retrieving and reporting data. The web-based application to be developed will replace the manual system with a more efficient, accurate, and easily accessible data management system. Equipped with automated reporting features and a dashboard to monitor NIB status in real-time, this application is expected to accelerate administrative processes, minimize data input errors, and provide ease for business owners to access information about their NIB status in a transparent and timely manner.